In-situ real-time monitoring of hydroxyethyl modification in obtaining uniform lignin derivatives. (5th January 2021) - Liu, Li-Yang; Bessler, Kim; Chen, Siwei; Cho, Mijung; Hua, Qi; Renneckar, Scott
Graphical abstract: Hydroxyethyl lignin is a promising lignin building block for preparing biobased polyesters and polyurethanes if the reaction is well-controlled. An in-situ real-time monitoring technique, using the volume of CO2 evolved during the hydroxyethyl modification of kraft lignin, was developed to monitor the modification, minimize the potential side reaction, enhance the quality of modified lignin, and reduce the workload on optimization. Highlights: Industrial sourced lignin can be readily chemically modified with cyclic carbonates. Developed real-time monitoring method to control the quality of hydroxyethyl lignin. Identified potential side reactions during the hydroxyethyl modification. Developed predictive model to reduce the workload on lignin derivatization. Proposed modification route that reduces the carbon footprint of pulping companies. Abstract: The chemical modification of kraft lignin is critical in developing value-added opportunities for the valorization of this biobased polymer. Hydroxyethyl modification is capable of improving both the chemical uniformity and thermal stability of lignin by substitution of phenolic and carboxylic acid groups. However, the main drawback of this reaction involving the cyclic carbonate as a derivatizing reagent was the occurrence of crosslinking arising from excess reaction time or temperature. Based on the 13 C and 2D 1 H– 13 C heteronucleaer single quantum correlation (HSQC) nuclear magnetic resonance (NMR) spectroscopy analysis, the potential condensation and side reactions were found to accompany the modification at longer reaction times, including the formation of carbonate linkage and intermolecular lignin condensation. These reactions caused a dramatic enhancement of molar mass, decreased solubility, and lowered the quality of modified lignin. Addressing this problem, we developed an in-situ, real-time monitoring method to control the quality of the derivatized lignin. This was achieved by identifying a high correlation between the volume of produced CO2 and the degree of hydroxyethylation of the lignin, as determined with NMR spectroscopy. Longer times led to evidence of carbonate linkage co-polymerization and increased molecular weight of the lignin. A predictive model was developed to reduce the workload on the optimization of the modification of different types of lignin resources and avoid side-product formation, based on the knowledge of the starting phenolic and carboxylic acid content of the materials and CO2 measurement. Finally, as ethylene carbonate can be treated as carbon storage chemical, the hydroxyethyl reaction can be readily integrated with the lignin recovery process, helping to reduce the carbon footprint and overall cost for pulping companies. In so doing, it provides a green route to develop functionalized aromatic renewable polymers for the polymer industry.